Green inheritance - Anthony Huxley (Four Walls Eight Windows, 1992)
The book highlights a deeping concern about the destruction that treatens our plant heritage, about the slender genetic base of the world's staple crops, about the dwindling last locations of wild resources with their unexplored potential as food, fuel, and medicine - in fact, about the fragile green inheritance we have pass on to our children